MASTERMobilityDB: A Persistence and Manipulation Layer for Trajectories of Multiple Aspects - Feller, Flaris Roland; Mello, Ronaldo dos Santos (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2024: Anais do XXXIX Simpósio Brasileiro de Bancos de Dados, 2024)
Spatiotemporal data about the movement of real-world entities collected from sensors and GPS devices, as well as their integration with other contextual georeferenced data, has produced voluminous and complex collections of trajectory data. These collections, known as multiple aspect trajectories (MATs), raise new challenges for moving object databases. This work introduces MASTERMobilityDB, a MAT persistence layer based on the MASTER representation model for MATs, built on top of MobilityDB database through the development of an API. A comparison with the state-of-the-art SecondoDB demonstrates that queries over MATs are expressed in MASTERMobilityDB more naturally and perform better. No similar proposal was found in the literature and industry.